PENGARUH LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. PERUSAHAAN EXPEDISI MAUMBI KOTA MANADO - Nikson Boose; Wehelmina Rumawas; Tinneke M. Tumbel (JURNAL ADMINISTRASI BISNIS, 2017)
The rapid technological developments bring changes in life and its development is inevitable. Is there any influence of work environment to employee performance at PT. Maumbi Expedition Company Manado City. To know the effect of work environment on employee performance, at PT. Maumbi Expedition Company Manado City. Work environment is a place where employees do activities every day. A conducive working environment provides a sense of security and enables employees to work optimally. Performance is a perwujup and work done by employees who are usually in use as a basis for assessment of employees or individuals. To analyze a problem must have to use a method or the right approach so that will in pengajian data process. What if researchers do research on a large population, while researchers want to examine about the population and researchers have limited funding, energy and time, the researchers used sampling techniques, 39 employees at PT. Maumbi mando expedition company. From the results of simple linear regression analysis in the form of the equation obtained Y = 37.35 + 0.12 X. Significantly very strong positive between work environment variables and employee performance variables. Company expedition maumbi manado city to continue to improve employee performance by doing strict supervision so that employees more obey the rules. Â Keywords: Work environment, employee performance